Évolution des milieux humides à Svalbarostunga (nord-est de l'Islande) en lien avec le climat et l'occupation humaine - Cyr-Parent, Isabelle (Université Laval, 2020)
Svalbarðstunga is a historic and official region that spans the territory between the Svalbarðsá and Sandárivers (northeastern Iceland). The principal farm of the region is known as Svalbarð’s farm. It is located downstream of the Svalbarðstunga watershed and has been a functioning farm for over 1000 years. Many secondary farms were established in the regiona as satellites of Svalbarð’s farm. The majority of this farms site was abandoned at various times, but the reasons for that are still unknow. Natural factors (e.g.,climate change, volcanism) and/or human factors (e.g., land degradation from overgrazing, epidemics) were the most likely causes of abandonment. The principal goal of this research is to document the impact of climate change and human activities on the environment in Svalbarðstunga. To achieve this aim, we studied the sedimentary record in a pond and in a wetland situated near the ruins of the ancient farms. The research includes the study of macrofossils, diatoms, geochemicals and sedimentary analysis. The wetland in the study was established soon after deglaciation, by 9190 years cal. BP. The local conditions were rich minerotrophicat that time. Subsequently, the site became relatively dry, but wet conditions were re-established by 470 years cal. BP. On the other hand, the pond in the study shows evidence of major perturbations between 1000 and 1350 AD such as deposition of a non-decayed peat level in a sedimentary sequence formed by gyttja. Taking into account the location of the study site, the practice of livestock breeding (mainly sheep) would have destabilized the land on the wathersed due to the overgrazing of the fluvioglacial and glacial deposits knolls that surround the pond. This process would have caused significant sedimentary accumulation in the pond. Svalbarðstunga est un nom de lieu historique et officiel qui identifie le territoire entre les rivières Svalbarðsá et Sandá (nord-est de l’Islande). En aval du bassin versant de Svalbarðsá, se situe la ferme principale de la région, ...